Unveiling the Mechanisms of Dispositional Mindfulness and Mental Health: A Study of Secondary School Teachers in Palu, Indonesia - Dhevy Puswiartika; Bau Ratu; Dini Rakhmawati; Azam Arifyadi; Munifah Munifah (Kuras Institute, 2026)
Teachers in Palu, Central Sulawesi, Indonesia, face complex professional pressures, including post-disaster recovery and a rapid transition to digital administration. This study aims to uncover the mechanisms linking mindfulness and mental health among secondary school teachers in Palu by exploring the mediating role of acceptance and the moderating role of age. A mixed-method approach with a sequential explanatory design was employed. The quantitative phase involved 66 junior and senior high school teachers selected through purposive sampling. The participants completed two instruments: the Dispositional Mindfulness at Work Scale and the Mental Health Inventory. Data were analyzed using linear regression and the PROCESS Macro for mediation and moderation testing, followed by thematic analysis in the qualitative phase to deepen the findings from the in-depth interviews with selected participants. The results indicated that correlation and simple regression analyses confirmed that dispositional mindfulness was a significant predictor of mental health, explaining 21% of its variance (B = 0.390, p < .001). Further analysis revealed a full mediation effect of the acceptance component, indicating that dispositional mindfulness requires an accepting attitude to effectively enhance teacher mental health. Additionally, age was a significant moderator (B = -0.048, p = .003), with the protective impact of dispositional mindfulness being notably greater for early-career teachers. Qualitatively, these mechanisms were found to be harmoniously integrated with the local wisdom of Nosarara Nosabatutu. Dispositional mindfulness emerged as the primary psychological resource supporting teacher resilience in a post-disaster, high-digital-demand environment. These findings provide an empirical basis for prioritizing mindfulness-based psychoeducation and interventions in guidance and counseling services.